2013
DOI: 10.1097/ico.0b013e318283453a
|View full text |Cite
|
Sign up to set email alerts
|

Studying Physician Knowledge, Attitudes, and Practices Regarding the Herpes Zoster Vaccine to Address Perceived Barriers to Vaccination

Abstract: Not only increased knowledge but also a change in attitudes and practice are needed to enhance implementation of national recommendations. To improve use of this vaccine, physicians including ophthalmologists need to recommend it more strongly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 28 publications
2
10
0
Order By: Relevance
“…The vaccine cost is high and is not covered by the National Immunization Program in Korea so far. Most study participants were concerned about the cost and were uncertain about the effectiveness of the HZ vaccine, which is consistent with findings from other studies [ 11 , 12 ]. Our findings were also comparable with previous studies of physician attitudes toward the human papillary virus vaccine, which is a relatively new and expensive vaccine, like the HZ vaccine.…”
Section: Introductionsupporting
confidence: 81%
“…The vaccine cost is high and is not covered by the National Immunization Program in Korea so far. Most study participants were concerned about the cost and were uncertain about the effectiveness of the HZ vaccine, which is consistent with findings from other studies [ 11 , 12 ]. Our findings were also comparable with previous studies of physician attitudes toward the human papillary virus vaccine, which is a relatively new and expensive vaccine, like the HZ vaccine.…”
Section: Introductionsupporting
confidence: 81%
“…Although previous studies have reported on perceptions, practices, and barriers to adult vaccination among primary care physicians [16–22], obstetricians/gynecologists (OB/GYN) [23–28], and pharmacists [29–32], the present study also assessed perceptions, practices, and barriers faced by clinicians and pharmacists, but in the context of implementing the individual components of the Standards.…”
Section: Introductionmentioning
confidence: 99%
“…22 BG and Vol were more likely to report cost as a barrier to vaccination, and BG, without the vaccine on formulary, expressed greater difficulties with ordering and administering the vaccine. As a result, BG physicians were more likely to respond that less than 10% of their patients received the HZ vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 The previously published baseline survey results show that only 66% of general internal medicine (GIM) physicians responded that HZ vaccination was an important clinical priority, and 48% reported that less than 10% of their patients received the HZ vaccine. 22 The top barrier to vaccination was cost to patients; and lack of awareness of national recommendations varied by provider setting.…”
Section: Introductionmentioning
confidence: 99%